The Probiotic Combination of Bifidobacterium longum subsp. infantis CECT 7210 and Bifidobacterium animalis subsp. lactis BPL6 Reduces Pathogen Loads and Improves Gut Health of Weaned Piglets Orally Challenged with Salmonella Typhimurium - Barba-Vidal, Emili; Castillejos, Lorena; Roll, Victor F. B.; Cifuentes-Orjuela, Gloria; Moreno Muñoz, José A.; Martín-Orúe, Susana M. (Frontiers in Microbiology, 2017)
Probiotics have been demonstrated to be useful to enhance gut health and prevent gastrointestinal infections in humans. Additionally, some multi-strain probiotic combinations have been suggested to have greater efficacy than single strains. The objective of this study is to demonstrate the potential of a combination of the probiotic strains: Bifidobacterium longum subsp. infantis CECT 7210 (brand name B. infantis IM1®) and B. animalis subsp. lactis BPL6 to enhance gut health and to ameliorate the outcome of a Salmonella challenge using a weaning piglet model. Seventy-two 28-day-old weanling piglets, 7.7 (±0.28) kg of body-weight, were distributed in a 2 × 2 factorial design; treated or not with the probiotic combination and challenged or not with the pathogen. Animals were orally challenged after an adaptation period (Day 8) with a single dose (5 × 108 cfu) of Salmonella Typhimurium. One animal per pen was euthanized on Day 12 (Day 4 post-inoculation [PI]) and Day 16 (Day 8 PI). All parameters responded to the challenge and 4 deaths were registered, indicating a severe but self-limiting challenge. Improvements registered in the challenged animals due to the probiotic were: increased voluntary feed-intake (P probiotic × challenge = 0.078), reduced fecal excretion of Salmonella (P = 0.028 at Day 1 PI and P < 0.10 at Days 3 and 5 PI), decreased rectal temperature (P probiotic × day = 0.048) and improvements in the villous:crypt ratio (P probiotic × challenge < 0.001). Moreover, general probiotic benefits were observed in both challenged and non-challenged groups: decreased diarrhea scores of the PI period (P = 0.014), improved fermentation profiles on Day 8 PI (increased ileal acetic acid [P = 0.008] and a tendency to lower colonic ammonia concentrations [P = 0.078]), stimulation of intestinal immune response by increasing villous intraepithelial lymphocytes (P = 0.015 on Day 8 PI) and an improved villous:crypt ratio (P = 0.011). In conclusion, the multi-strain probiotic had a positive effect on reducing pathogen loads and alleviating animals in a Salmonella challenge. In addition, enhanced gut health and immunity was recorded in all animals receiving the probiotic, indicating an improvement in the post-weaning outcome.